2000
DOI: 10.1161/01.cir.102.3.344
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptor Subtypes Differentially Affect Apoptosis in Adult Rat Ventricular Myocytes

Abstract: BACKGROUND-Catecholamine-induced apoptosis is mediated by activation of the beta-adrenergic signaling pathway. We tested the hypothesis that beta(1)- and beta(2)-adrenergic receptor (AR) subtypes differentially affect apoptosis in adult rat ventricular myocytes in vitro. METHODS AND RESULTS-Myocytes were first exposed to norepinephrine (NE) alone (10 mcmol/L) or NE+atenolol (AT) (10 mcmol/L) for 12 hours. AT, a beta(1)-selective AR antagonist, abolished the NE-induced increase in nick end-labeling (TUNEL)-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(127 citation statements)
references
References 34 publications
6
117
1
3
Order By: Relevance
“…Both pathways have been shown to mediate hypertrophy in myocardial cells. 43,44 In this study, after AR-a 1 blockade with carvedilol, the expression of Gqa protein, PKC-a and PKC-d was decreased significantly in the carvedilol-treated group, which suggested that Gqa, PKC-a and PKC-d were the main molecules linked to AR-a 1 in the signal transduction pathway. In contrast, the expression of AR-b 1 and AR-b 2 was increased after treatment, followed by a normalized Gsa protein expression and decreased PKA level, and these effects were the most significant in the carvediloltreated group.…”
Section: Discussionmentioning
confidence: 48%
“…Both pathways have been shown to mediate hypertrophy in myocardial cells. 43,44 In this study, after AR-a 1 blockade with carvedilol, the expression of Gqa protein, PKC-a and PKC-d was decreased significantly in the carvedilol-treated group, which suggested that Gqa, PKC-a and PKC-d were the main molecules linked to AR-a 1 in the signal transduction pathway. In contrast, the expression of AR-b 1 and AR-b 2 was increased after treatment, followed by a normalized Gsa protein expression and decreased PKA level, and these effects were the most significant in the carvediloltreated group.…”
Section: Discussionmentioning
confidence: 48%
“…In a subsequent study apoptosis was shown to be mediated through the b 1 -AdrR, via e ects on cyclic AMP (Communal et al, 1999). Zaugg et al (2000) also demonstrated that it is the b 1 -AdrR which mediates the apoptotic response to NE. This ®nding is particularly relevant in light of the observation that transgenic animals expressing b 1 -AdrR, even at relatively low levels, develop heart failure associated with apoptosis (Engelhardt et al, 1999;Bisognano et al, 2000).…”
Section: Gas Signaling In Apoptosis and Failurementioning
confidence: 93%
“…However, substantial evidence from the literature points to significant differences between β 1 and β 2 -adrenergic receptor subtypes and their ability to stimulate apoptosis, or programmed cell death, in isolated cardiac myocytes and in vivo experiments performed in knockout mice lacking β 1 , β 2 or both subtypes (Patterson et al 2004). β 1 -adrenergic receptor stimulation results in an increased cardiac myocyte apoptosis via cAMP-dependent mechanism (Communal et al 1998(Communal et al , 1999, whereas stimulation of β 2 -subtype inhibits apoptosis via a Gi-coupled pathway involving PI3K and Akt-PKD (Chesley et al 2000, Zaugg et al 2000, Zhu et al 2001. These findings have interesting clinical implications for heart failure therapy, since they provide cellular and molecular mechanisms that underline the beneficial therapeutic effects of some β-adrenergicreceptor antagonists, and provide the rationale for combining β 1 -subtype specific blockade with β 2 -subtype activation.…”
Section: The Cardiac β-Adrenergic Pathway In Heart Failurementioning
confidence: 99%